An investigation of the lower Permian middle Ecca ammonite locality at Alleta, Natal - McLachlan, I. R. (Bernard Price Institute for Palaeontological Research, 1977)
The problematic ammonite Paraceltites bowdeni Teichert & Rilett has been recorded only from the Alleta iron-ore mine near Dundee in Natal. It is unique in the Early Permian Ecca Series as it suggests a normal salinity for the depositional environment of sediments that have yielded no other clearly marine fossils. An investigation of the matrix of the specimen slabs, however, yields information which is incompatible with equivalent data from the Alleta mine and the Ecca sediments in general. The matrix contains the distinctive pollen Classopollis which is not known from elsewhere in the world in deposits older than Late Triassic. Comparative tests of the degree of thermal diagenesis of the contained organic material suggests that the ammonite specimens have not been subjected to the same degree of alteration as the sediments at the Alleta mine. Results of other tests have not been definitive but do not contradict the suggestion that the ammonites were mistakenly accredited to the A1leta mine. It is concluded that the ammonites derived originally from sediments of Late Triassic to Early Jurassic age at an unknown locality outside of South Africa.
Main artice
Keywords: ammonite; Alleta; South Africa; Permian; ecca